The Use of CFD Methods in the Shipbuilding Industry and Their Benefits: Array - Chirosca, Ana-Maria; Rusu, Liliana (Acta Universitatis Danubius. Œconomica, 2021)
CFD (Computational Fluid Dynamics) is a branch of fluid mechanics that uses numerical methods and algorithms to analyze and solve problems involving fluid flow. In general, in the shipbuilding industry, when it is desired to validate a ship model, in order to determine its resistance, as well as the ship's behavior on waves, model tests are used in towing tanks. But resistance in calm waters and resistance in waves are not the only naval characteristics studied in the towing tanks. There are also tests in the basin and cavitation tunnels for testing propellers, tests for vessel's maneuvering behavior, and much more. Unfortunately, these tests involve high prices and last a long time, and in the future the aim is to replace these tests with CFD simulations that last much less and involve much lower costs, and the accuracy of the results is satisfactory. This study provides an overview of CFD simulations, their benefits and disadvantages.